Wages, income and living standards in Western India, 1510-1570 - Matos, P. T. de (2022)
This chapter examines wage and income development and its effects on living standards in 16th-century Western India, for which there were no wages known prior to those recorded in the Ain-i-Akbari (c. 1595). The 16th century is particularly important because India underwent a great institutional renaissance during the rule of the Sur dynasty, and later under Akbar, the greatest of all Mughal emperors. It is also the century in which intensive maritime con- tacts between Europe and Asia were established. This study aims to integrate Western India in a wider global discussion about welfare and living standards in South Asia, the so-called Great Divergence debate. We will demonstrate that there was an increase in both nominal and real wages of unskilled Indian labourers along the Indian West Coast from 1510 to 1570 (particu- larly around the middle of the 16th century), and we will link this to the epochal change that took place in India in that period.